Teaching in a combined class from a small rural school - an example from practice - Petrovic, Zlata Z (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
This text places the work experience from one rural school, a displaced class with combined teaching, in the broader context of demographic trends of contemporary social moment and teaching practices which are still taking place in Serbia. The analysis is illustrated by an example from practice. It can be said that this presents a case study of work in the unassigned class in the village of Okruglica in Municipality of Svrljig. The school work is analysed through the following categories: current working conditions in the school, students' success, past, present and future of this combined class, the advantages and disadvantages of working in the combined class, the difficulties with which teacher is faced during work.
Keywords: rural school; TEACHING; elementary school; teaching practice; combined class